PERBANDINGAN MODEL PEMBELAJARAN MIND MAPPING BERBANTU LKS DENGAN METODE CERAMAH TERHADAP HASIL BELAJAR SISWA - Putra, Eric Dwi; Lutfiyah, Lutfiyah (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2020)
This study aims to show differences in the learning outcomes of applying mind mapping learning with lectures. This study took a population in Class VIII SMP N Open 1 Gumukmas. The sample in this study was taken randomly, namely class VIII TKA Al Aufa as many as 16 students in the class with mind mapping model with LKS and class VIII TKB Baiturrohman 14 students in the class with conventional method. Data collection used test method. Data analysis technique used descriptive statistical analysis. From the results of the research and data analysis, it can be concluded that there are differences in the learning outcomes of the class with mind mapping model with LKS compared to the class with conventional method. This is evidenced by the average value of the class with mind mapping model with LKS getting 80.25 and the class with conventional method of 68.85.